Solving Simple Hormonic Problems Using Adomian Decomposition Method - Irfan Ul Haq; Sandeep Kumar Tiwari; Pradeep Porwal; Naveed Ul Haq (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this research paper, we propose classical numerical technique for solving some simple harmonic problems arising in some applications of science. Adomian decomposition method (ADM) are used. Some numerical examples have been solved to illustrate the accuracy and efficiency of this numerical method.
Keywords: Adomian Decomposition Method; Simple Harmonic Equations; Differential Equations